Middle Manager’s Commitment to Change: a Qualitative Study - Evi Kurniasari Purwaningrum; Fendy Suhariadi; Fajrianthi Fajrianthi (Journal of Educational, Health and Community Psychology, 2019)
AbstractIn times of change, it is very important for middle managers to commit to change because middle managers have a strategic role in the formulation and implementation of change. This study aims to explore the middle manager’s commitment to change at the beginning of the change period and one year after the initiation of change. This research uses a phenomenological qualitative approach and the longitudinal method. Data was taken using semi-structured interviews at nine middle managers. The result shows three main themes: (1) Middle managers' initial commitment to change is influenced by their views on the importance of change and middle managers experience at the beginning of change, (2) there is a change in commitment to change after one year of organizational change, (3) factors that are influenced change in middle manager’s commitment to changes. The findings in this study are expected to be a meaningful contribution to understanding the commitment to change among middle managers.Keywords: Organizational changes, agents of changes, qualitative study.